THE FOUR-PHASE AFM ASSEMBLAGE STAUROLITE–ALUMINUM SILICATE–BIOTITE–GARNET: EXTRA COMPONENTS AND IMPLICATIONS FOR STAUROLITE–OUT ISOGRADS - Giaramita M.J.; Day H.W. (My University, 1991)
The prograde disappearance of staurolite can be described in the model system K2O-FeO-MgO-Al2O3-SiO2-H2O (KFMASH) by the reaction: staurolite + muscovite + quartz = biotite + aluminum silicate + garnet + water. The common occurrence and world—wide distribution of the assemblage staurolite-biotite-aluminum silicate-garnet (SBAG) in quartz-mica-schist suggest that the model reaction may be over-simplified. Previous workers have suggested that the SBAG assemblage (1) is a strictly divariant assemblage that buffered water activity, (2) is stabilized by non-KFMASH components, and (3) did not attain equilibrium. We used least-squares regression to show that balanced reactions do not exist among the minerals in samples of SBAG assemblages from Califonia and New England. The absence of reaction relationships can be explained by imbalances in two or three of the minor elements Zn, Mn, and either Ca or Na. The assemblage is apparently stabilized by non-KFMASH components. Criteria for mapping staurolite-out isograds that represent the conditions of the KFMASH staurolite-out reaction depend on which of the four phases is the ‘extra’ phase, and require an understanding of the thermodynamic effects of all the ‘extra’ components. Our results suggest that transition zones of SBAG assemblages near staurolite-out isograds are the result of ‘extra’ components. However, it is uncertain whether ?H2O of fluids in equilibrium with SBAG assemblages varied across such zones.